Validating Fin Ray Microchemistry as a Tool to Reconstruct the Migratory History of White Sturgeon. Issue 5 (19th April 2017) - Sellheim, K.; Willmes, M.; Hobbs, J. A.; Glessner, J. J. G.; Jackson, Z. J.; Merz, J. E.
Abstract: The objective of this study was to validate the use of fin ray strontium isotope ratios ( 87 Sr: 86 Sr) via laser ablation (LA) to resolve fine‐scale movement patterns in sturgeons (Acipenseridae) during freshwater rearing in early life stages. We conducted a laboratory experiment in which juvenile White Sturgeon Acipenser transmontanus were exposed to two water sources exhibiting distinctive 87 Sr: 86 Sr isotope values (American River and Putah Creek, California) over weekly time periods to understand how water exposure histories are archived in pectoral fin rays. Using LA multicollector inductively coupled plasma mass spectrometry with a laser diameter of 65 µm, we detected distinct shifts in fin ray 87 Sr: 86 Sr values to match a water source in fish that were exposed for 2, 4, 6, and 12 weeks. Fin ray 87 Sr: 86 Sr values matched the new water source after 21.7 d (SD = 7.8; range = 11–36 d) of exposure. The lower limit of this estimate was constrained by the rate of fin ray growth as well as the LA spot size. Additionally, we assessed how diet affected fin ray 87 Sr: 86 Sr values by feeding a marine‐derived pellet feed commonly used in aquaculture to a subset of White Sturgeon, while others were fed a diet consisting of fish with 87 Sr: 86 Sr values that matched their respective water source. Generally, we observed only a minor influence of diet, but there was some variability across individual fish in the effect of diet on the resulting fin ray 87 Sr: 86 Sr value. As with any geochemical analytical technique, fin ray microchemistry has some limitations related to individual variability in fin ray growth and development; however, it is a promising approach to reconstructing sturgeon migratory history by using a nonlethal sampling method. Received December 16, 2016; accepted April 13, 2017 Published online June 23, 2017